Genetic diversity of wheat (Triticum aestivum L.) plants-regenerants produced by anther culture - D. Grauda; K. Žagata; G. Lanka; V. Strazdina; V. Fetere; N. Lisina; N. Krasnevska; O. Fokina; A. Mikelsone; R. Ornicans; I. Belogrudova; I. Rashal (Вавиловский журнал генетики и селекции, 2016)
The study of genetic diversity of wheat (Triticum aestivum L.) plants-regenerants produced by anther culture method from hybrids involved in the Latvian wheat breeding programme was performed. Flow cytometry was used to test ploidy of 3×103 cells of each green plantregenerant, and universal retrotransposon based iPBS (inter primer binding sites) method were used to establish genetic diversity of plants-regenerants. Progenies of 13 genetically distant hybrids were involved in the study. Most of plants-regenerants have leaves with mixoploid cells. Seeds were formed only by plants-regenerants that had cells with (2n = 6x) ploidy. Majority of fertile plantsregenerants have more than 40 % of hexaploid (6x) cells. The percentage of 6x cells in plants-regenerants and diversity in cell ploidy demonstrated association with mother plant (hybrid) genotype. Percent of spontaneous diplodization was also genotype-dependent. In this experiment colchicine treatment had no significant influence on outcome of fertile plants- regenerants. New dominant allele in a hybrid plant was found in comparison with both parents what indicated possible retrotransposon moving. Genetic diversity of the plants-regenerants obtained in anther culture is a combination of parent’s allele segregation and somaclonal variation.